Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Free Cash Flow Terhadap Kebijakan Hutang Pada Perusahaan Sub Sektor Kosmetik Dan Keperluan Rumah Tangga Yang Terdaftar Di Bursa Efek Indonesia - Karnila Ali; Fitriani; Dina Fitriani (Universitas Muhammadiyah Metro, 2024)
This study was aimed at determining whether there was an effect on company size,profitability, and free cash flow on debt policy in cosmetics and household goods sub-sectorcompanies in the 2019-2021 period, where the DER value of the company has fluctuated andeven increased and the company has experienced a decrease in revenue. This research usedquantitative methods. The sampling technique in this study used purposive sampling, namelythe sampling technique with certain considerations according to research needs. The sampleused in this study amounted to 6 companies. The study was analyzed by descriptive statisticalanalysis and the classic assumption test which consisted of the normality test,multicollinearity test, autocorrelation test, and heteroscedasticity test. Testing the researchhypothesis was carried out through panel data regression testing with the common effectmodel, fixed effect model, and random effect model techniques. The selection of thistechnique used the Chow test and the Hausman test, so the model chosen in this study was thefixed effect model. Furthermore, hypothesis testing was carried out through the t test, f test,and the coefficient of determination test (R2). The results of the study showed; Company sizehas no effect on debt policy, Profitability has a negative and significant effect on debt policy, Free cash flow has a positive and significant effect on debt policy, and Firm size,profitability, and free cash flow have a significant effect on debt policy.